Analysis of Increasing CO2 Emissions and Economic Activity: An Empirical Investigation in 4 ASEAN Countries - Muhammad Adi Adrian; Saifudin Zuhri; Sucihatiningsih Dian Wisika Prajanti (International Conference on Science, Education, and Technology, 2023)
The increase in global temperature and climate change that has occurred over the past decade is the result of increased CO2 emissions. Several factors such as gross domestic product, population, deforestation, and energy consumption are considered to be the most influential in increasing CO2 emissions. This paper uses panel data analysis to analyze the relationship between economic growth (GDP), population, deforestation, and energy consumption on increasing CO2 emissions in four ASEAN countries (Indonesia, Malaysia, Thailand, Vietnam) for the period 2001-2021. The research method used is panel data regression with the Fixed Effect Model (FEM). Using FEM, the results show that partially economic growth (GDP) and energy consumption have a positive effect on CO2 emissions. Meanwhile, population and deforestation have no influence on CO2 emissions. But simultaneously has a confidence level of 98.84% where the variation in the percentage change in CO2 emissions in the four countries in ASEAN is explained by the variables of economic growth (GDP), population, deforestation, and energy consumption by 98.84% and the remaining 1.16% is influenced by other variables outside these variables. Finally, the panel data results show that there is a significance of energy consumption and economic growth in the four ASEAN countries that have implications for CO2 emissions.